Method for preparing water-soluble composite salt core based on slurry direct-writing forming 3D printing technology

Through slurry direct writing forming 3D printing technology and step-by-step sintering process, complex core materials are directly formed, solving the high strength, precision forming and environmental protection requirements of low-melting point alloy casting core materials such as aluminum (magnesium) in the existing technology, and achieving efficient, precise and environmentally friendly water-soluble composite salt core preparation.

CN119500988AActive Publication Date: 2025-02-25CHINA UNIV OF GEOSCIENCES (WUHAN) +1

Patent Information

Application Number
CN202411626602.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-25
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The prior art is difficult to meet the high strength, precision forming, easy cleaning and environmental protection requirements of complex core materials for low melting point alloy castings such as aluminum (magnesium). The traditional preparation process has problems of low preparation efficiency, high cost and insufficient performance.

Method used

The slurry direct writing forming 3D printing technology is adopted to coordinate the composition of salt core material, extrusion direct writing 3D printing forming and step-by-step sintering processes, and the complex special-shaped hole and runner structure are directly formed, avoiding the accuracy error caused by core assembly.

Benefits of technology

It realizes high-strength, precision forming and environmentally friendly water-soluble composite salt core, solves the overall forming problem of complex core materials, improves bending strength and impact toughness, and meets the need for rapid and die-free overall direct forming of complex cast cores.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500988A_ABST
    Figure CN119500988A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of casting, and particularly relates to a method for preparing a water-soluble composite salt core based on a slurry direct-writing forming 3D printing technology. A water-soluble composite salt core material for low-melting-point alloy casting is composed of pretreated water-soluble inorganic salt, a binder and an additive, the pretreated water-soluble inorganic salt is obtained by mixing a coating solution and inorganic salt powder, and the mass percent of the coating solution and the inorganic salt powder is 100%. The ratio of the pretreated water-soluble inorganic salt to the binder to the additive is (60-80%): (20-30%): (0-10%). Compared with a traditional method for preparing a water-soluble salt core, the water-soluble composite salt core material has the advantages that the water-soluble salt core formed through slurry direct writing can be used for rapidly forming parts without a mold, the process is simple, the raw material cost is low, the equipment requirement is low, and rapid and accurate mold-free forming of high-precision complex salt cores can be achieved; the problem that complex salt cores are difficult to integrally form is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of casting technology, and more specifically, relates to a method for preparing a high-strength water-soluble composite salt core by 3D printing of slurry for casting low-melting-point alloys such as aluminum (magnesium). Background Art

[0002] With the rapid development of my country's aviation, aerospace, automobile manufacturing, and 5G communications, the demand for complex thin-walled precision castings of low-melting-point alloys such as aluminum (magnesium) is also increasing. Such castings often have complex inner cavity structures, some of which are basically closed or have many slender curved channels of different shapes. Prefabricated cores are required to cast the complex inner cavity structure and remove the core after the casting is formed. In order to form high-quality precision castings, higher requirements are placed on the performance of the casting core and its forming and cleaning methods.

[0003] The casting core must have high room temperature strength and dimensional accuracy, good high temperature stability and air permeability, small gas emission, and excellent post-casting disintegration and cleaning performance; the commonly used casting core materials such as resin sand cores, silicon oxide and alumina-based ceramic cores cannot meet the above performance requirements at the same time, and all need to use mixed alkali method, alkali solution method, pressure core removal method and hydrofluoric acid method to clean the residual cores in the inner cavity of the casting and the curved channels. It is very difficult to clean the residual cores in the nearly closed inner cavity of the casting. Among the above core cleaning methods, some will corrode the casting, some will produce toxic substances to pollute the environment, and some have complex core removal processes and require special equipment (such as pressure core removal method). Water-soluble salt core technology can solve the problem of cleaning casting core materials very well. After the casting is formed, the residual core can be quickly cleaned by dissolving it with water, which can save labor and improve the working environment.

[0004] At present, it is difficult to directly form this type of complex salt core as a whole. Traditional preparation processes include melt casting, pressing and sintering, and bonding forming. The melt casting method requires block forming and assembly through a mold, which is a complex process and has low preparation efficiency; the pressing and sintering method has high preparation costs, complex preparation processes, and high equipment requirements; the salt cores prepared by the bonding forming method have low mechanical properties and low water solubility rates. Therefore, the water-soluble salt cores prepared by traditional processes are difficult to meet the requirements of die-casting production, and the preparation of integrated, complex, and precise water-soluble salt cores has become a key problem in the manufacture of cavity die-castings of low-melting-point alloy castings such as aluminum (magnesium).

[0005] CN 104399865A discloses a water-soluble graphite composite salt core material, a graphite composite salt core and a preparation method thereof, which are mainly used for casting of cooling oil channels in aluminum pistons. The material of the graphite composite salt core includes a water-soluble metal halide (a single metal halide or a mixture of multiple metal halides) and graphite powder, and the preparation method is a pressing and sintering method. The salt core prepared by the method has high strength and low shrinkage, but the graphite powder and the metal halide are easily mixed unevenly, resulting in stratification of the salt core, which affects the performance of the salt core.

[0006] CN 106670376A discloses a high-strength composite salt core for casting low-melting alloys, wherein the components of the water-soluble salt core include water-soluble inorganic salts and reinforcing agents, wherein the inorganic salts include a low-melting inorganic salt and more than one high-melting inorganic salt. The low-melting inorganic salts are potassium nitrate and sodium nitrate, and the high-melting inorganic salts are potassium chloride, potassium bromide, sodium chloride and sodium bromide. The reinforcing agent includes one or more of dalin sand, refractory mud powder, glass fiber powder, kaolin, quartz powder, bentonite, alumina powder and high-alumina bauxite. The preparation of the salt core adopts a melt casting method, and the prepared salt core has high strength and low moisture absorption rate. However, the low-melting salt determines the melting point of the overall salt core, so the salt core is only suitable for casting low-melting alloys, and cannot meet the casting requirements of low-melting alloys such as aluminum (magnesium).

[0007] CN 115815532A discloses a water-soluble salt core material and a preparation method and application thereof, wherein the components of the water-soluble salt core include an inorganic salt and a binder, wherein the inorganic salt is a single salt with a high melting point, including one of sodium chloride, potassium chloride, sodium sulfate or potassium sulfate, and the binder includes two or more of an organic binder and an inorganic binder, one of which is bentonite. The salt core is prepared by extrusion molding. Although the preparation process is simple and a water-soluble salt core with a complex shape can be formed, the salt core composed of a single inorganic salt has a lower strength than a composite salt core, and the mechanical properties need to be improved.

[0008] The preparation method of the above-mentioned water-soluble salt core includes traditional preparation processes and emerging preparation processes. However, in order to achieve high-efficiency and high-quality simultaneous production of water-soluble salt cores of low-melting-point alloy castings such as aluminum (magnesium) with slender and curved internal channels and complex spatial structures, it is necessary to further optimize the material composition and preparation method of the salt core and seek a more complete preparation plan. Summary of the invention

[0009] In view of the shortcomings of the prior art and the need for improvement, the present invention provides a method for preparing a water-soluble composite salt core based on slurry direct writing 3D printing technology, which is mainly used for low-melting-point alloy castings such as aluminum (magnesium) with complex internal structures. By synergistically regulating parameters such as salt core material composition, extrusion direct writing 3D printing and step-by-step sintering process, complex special-shaped holes, runners and other structures can be directly formed as a whole, avoiding the precision error caused by core assembly, and has a good application prospect in the development of complex core material systems and new products, and can be used for the moldless rapid overall direct forming of complex casting cores.

[0010] A water-soluble composite salt core material for low melting point alloy casting, comprising the following components:

[0011] Pre-treat water-soluble inorganic salts, binders and additives, wherein the pre-treat water-soluble inorganic salts are obtained by mixing a coating solution with inorganic salt powder, and in terms of mass percentage, pre-treat water-soluble inorganic salts: binder: additives = 60%-80%: 20%-30%: 0%-10%.

[0012] Further, the mass percentage of the inorganic salt powder to the coating solution is 40%-60%:40%-60%. Further, the inorganic salt powder includes two or more of sodium sulfate, potassium sulfate, sodium carbonate, potassium carbonate, calcium carbonate, sodium chloride, potassium chloride, magnesium chloride, calcium chloride or barium chloride, and the melting point of the inorganic salt powder is 450-1200°C;

[0013] The particle size of the inorganic salt powder is 500-3000 mesh;

[0014] The coating solution is prepared from polydimethylsiloxane and anhydrous ethanol.

[0015] Furthermore, the binder is one of polyvinyl alcohol aqueous solution, polyethylene glycol aqueous solution, polyacrylamide aqueous solution, methyl cellulose aqueous solution, epoxy resin aqueous solution, polyvinyl pyrrolidone-anhydrous ethanol solution, and polyacrylic acid-anhydrous ethanol, and the concentration of the binder solution is 1% to 25%.

[0016] Furthermore, the additive is a mixture of an enhancer, a dispersant and a defoamer, and in terms of mass percentage, the enhancer: the dispersant: the defoamer = 97.5%-99.5%: 0.5%-1.5%: 0%-1%. ;

[0017] The reinforcing agent is one or more of bauxite powder, corundum powder, mullite powder, zirconium oxide powder, quartz powder, titanium oxide powder, sericite or glass fiber, and the particle size of the reinforcing agent is 300-1250 meshes;

[0018] The dispersant is one of ammonium polyacrylate or sodium dodecylbenzene sulfonate;

[0019] The defoaming agent is a silicone defoaming agent.

[0020] A method for preparing a water-soluble composite salt core by 3D printing of slurry for low melting point alloy casting, specifically comprising the following steps:

[0021] S1. 3D printing of the salt core blank: preparing salt-based raw materials, grinding the salt-based raw materials sufficiently to obtain salt-based slurry, and using slurry direct writing forming equipment to 3D print the salt-based slurry to obtain a salt core blank;

[0022] Wherein, the salt-based raw material is the above-mentioned water-soluble composite salt core material or a mixture of a binder and a dispersant;

[0023] The inner diameter of the printing needle is 0.41mm~1.55mm, and the extrusion pressure is 5psi~50psi;

[0024] S2. Sintering of the water-soluble composite salt core: The salt core blank is subjected to natural drying, baking and sintering treatments in sequence to obtain a water-soluble composite salt core.

[0025] Furthermore, in step S1, when the salt-based raw material is a water-soluble composite salt core material, the preparation method of the salt-based slurry is:

[0026] The inorganic salt powder is coated with a coating solution to obtain a pretreated water-soluble inorganic salt, and the pretreated water-soluble inorganic salt, a binder solution and an additive are uniformly mixed to obtain a premixed solution, wherein the additive is a mixture of a reinforcing agent, a dispersant and a defoaming agent, and the mass percentage of each component is as follows:

[0027] Pretreatment water-soluble inorganic salt: binder: additive = 60%-80%: 20%-30%: 0%-10%.

[0028] Further, in step S1, when the salt-based raw material is a mixture of a binder and a dispersant, graphite powder is added to the mixture, and the mass percentages of graphite powder, binder and dispersant are 70%-75%: 24%-29.5%: 0.5%-1% by mass percentage, and:

[0029] The dispersant is one of ammonium polyacrylate or sodium dodecylbenzene sulfonate;

[0030] The binder is one of polyvinyl alcohol aqueous solution, polyethylene glycol aqueous solution, polyacrylamide aqueous solution, methyl cellulose aqueous solution, epoxy resin aqueous solution, polyvinyl pyrrolidone-anhydrous ethanol solution and polyacrylic acid-anhydrous ethanol.

[0031] Furthermore, the drying temperature condition is 40°C to 90°C, and the drying time is 12h to 24h; the sintering adopts a combination of step-by-step sintering and liquid phase sintering, and the final sintering temperature is 450 to 1200°C.

[0032] The water-soluble composite salt core is prepared by the above method.

[0033] In general, the water-soluble salt core material and preparation method of the present invention have the following main advantages compared with the prior art:

[0034] (1) Compared with the traditional method of preparing water-soluble salt cores, the advantage of slurry direct writing forming water-soluble salt cores is that parts can be quickly formed without molds, and the process is simple, the raw material cost is low, and the equipment requirements are low. It can achieve moldless rapid and precise forming of high-precision complex salt cores, obtain salt cores with complete structure, dense organization and high precision, and solve the problem of difficult overall forming of complex salt cores.

[0035] (2) In order to solve the problem that it is difficult to simultaneously improve the flexural strength and impact toughness of the existing salt core, the flexural strength and impact toughness of the composite salt core are simultaneously improved by the multi-phase hybrid coupling of inorganic salts and reinforcing agents.

[0036] (3) After the inorganic salt powder is coated, a hydrophobic barrier is formed on the surface of the inorganic salt powder particles to prevent the inorganic salt from dissolving when using a water-based binder, thereby expanding the selection range of the binder solution and having more environmental and cost advantages.

[0037] (4) The properties of the blank, such as complete formability, surface quality, dimensional accuracy, and strength, can be coordinated and controlled by adjusting the direct writing forming parameters (filling rate, printing speed, needle inner diameter, and filling line angle, etc.).

[0038] (5) The sintering process adopts a combination of step-by-step sintering and liquid phase sintering. Step-by-step sintering can reduce cracks and deformation caused by sudden temperature changes by controlling the heating rate and holding time; liquid phase sintering helps to evenly distribute and better bond the particles, further optimize the microstructure of the material, improve the bending strength of the salt core, and avoid over-sintering. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The present invention is a flow chart of the preparation process of the water-soluble composite salt core. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical scheme and advantages of the present invention clearer, the specific embodiments of the present invention are further described below in conjunction with specific examples and drawings. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.

[0041] The physical and chemical parameters of the sodium chloride powder used in the present invention are shown in Table 1:

[0042] Table 1

[0043]

[0044] The physical and chemical parameters of the sodium carbonate powder used in the present invention are shown in Table 2:

[0045] Table 2

[0046]

[0047] The physical and chemical parameters of the magnesium chloride powder used in the present invention are shown in Table 3:

[0048] Table 3

[0049]

[0050] The physical and chemical parameters of the calcium chloride powder used in the present invention are shown in Table 4:

[0051] Table 4

[0052]

[0053] The physical and chemical parameters of the barium chloride powder used in the present invention are shown in Table 5:

[0054] Table 5

[0055]

[0056]

[0057] The physicochemical parameters of the potassium chloride powder used in the present invention are shown in Table 6:

[0058] Table 6

[0059]

[0060] The present invention is to protect a water-soluble composite salt core material for low melting point alloy casting, which is composed of the following components:

[0061] Pre-treat water-soluble inorganic salts, binders and additives, wherein the pre-treated water-soluble inorganic salts are obtained by mixing a coating solution with an inorganic salt powder, and in terms of mass percentage, pre-treat water-soluble inorganic salts: binder: additives = 60%-80%: 20%-30%: 0%-10%, inorganic salt powder: coating solution = 40%-60%: 40%-60%.

[0062] The inorganic salt powder includes two or more of sodium sulfate, potassium sulfate, sodium carbonate, potassium carbonate, calcium carbonate, sodium chloride, potassium chloride, magnesium chloride, calcium chloride or barium chloride, and the melting point of the composite inorganic salt multi-element system is 450-1200°C; the particle size of the inorganic salt powder is 500-3000 mesh; the coating solution is an organic silicon solution. The coating solution is an organic silicon solution, which is prepared from polydimethylsiloxane (PDMS) and anhydrous ethanol, and the concentration is 50wt.%. The binder is one of a polyvinyl alcohol aqueous solution, a polyethylene glycol aqueous solution, a polyacrylamide aqueous solution, a methylcellulose aqueous solution, an epoxy resin aqueous solution, a polyvinyl pyrrolidone-anhydrous ethanol solution, and a polyacrylic acid-anhydrous ethanol, and the concentration of the binder solution is 1% to 25%.

[0063] The additive is a mixture of a reinforcing agent, a dispersant and a defoaming agent. The reinforcing agent can improve the bending strength and thermal stability of the salt core; the addition of the dispersant can prevent the agglomeration of particles in the slurry, improve the deposition quality, and improve the surface flatness and forming accuracy of the salt core; the defoaming agent can eliminate bubbles in the slurry, prevent bubbles from remaining in the formed structure during the slurry mixing and extrusion process, and improve the density and structural integrity of the salt core.

[0064] The reinforcing agent is one or more of bauxite powder, corundum powder, mullite powder, zirconium oxide powder, quartz powder, titanium oxide powder, sericite or glass fiber, and the particle size of the reinforcing agent is 300-1250 meshes;

[0065] The dispersant is one of ammonium polyacrylate or sodium dodecylbenzene sulfonate;

[0066] The defoaming agent is a silicone defoaming agent.

[0067] The water-soluble composite salt core material of the present invention is prepared by a slurry direct writing forming process, can have a complex and elongated structure, and can be quickly formed without a mold.

[0068] Another aspect of the present invention provides a method for preparing a high-strength water-soluble composite salt core based on slurry direct writing technology, wherein the salt core is prepared from the water-soluble composite salt core material used for casting low-melting point alloys such as aluminum (magnesium).

[0069] A method for preparing a water-soluble composite salt core by 3D printing of slurry for low melting point alloy casting, comprising the following steps:

[0070] (1) Preparation of salt-based slurry

[0071] The salt-based slurry of the present invention may be a mixture of the above-mentioned water-soluble composite salt core material or a binder and an additive;

[0072] When the salt-based slurry is a water-soluble composite salt core material, the preparation method of the salt-based slurry is:

[0073] The inorganic salt powder is coated with a coating solution to obtain a pretreated water-soluble inorganic salt. The pretreated water-soluble inorganic salt, the binder solution and the additive are uniformly mixed to obtain a premixed solution, wherein the additive is a mixture of a reinforcing agent, a dispersant and a defoaming agent, and in terms of mass percentage, the pretreated water-soluble inorganic salt: binder: additive = 60%-80%: 20%-30%: 0%-10%. The premixed solution is transferred to a ball milling jar and placed in a planetary ball mill for full ball milling (the weight ratio of the ball milling beads to the salt-based slurry is 1:5), the planetary ball mill speed is 180-300r / min, the ball milling time is 8h-15h, and after taking it out, a salt-based slurry suitable for extrusion direct writing is obtained.

[0074] When the salt-based slurry is a mixture of a binder and a dispersant, the preparation method of the salt-based slurry is:

[0075] Graphite powder is added to the mixture, and in terms of mass percentage, the mass percentages of graphite powder, binder and dispersant are 70%-75%: 24%-29.5%: 0.5%-1%.

[0076] (2) 3D printing of salt core blanks

[0077] The salt-based slurry is loaded into the extrusion barrel of the slurry direct writing forming equipment. The motion trajectory of the extruder head and the extrusion state are controlled by a computer control program and a dispensing machine. The salt-based slurry is deposited on the substrate according to the preset route to form a salt core blank. Methyl silicone oil needs to be applied to the surface of the substrate to prevent the blank from drying too quickly and causing cracks, and to facilitate the separation of the blank from the substrate.

[0078] (3) Sintering of water-soluble composite salt core

[0079] After 12 hours of natural drying, the salt core blank is transferred to a drying oven for drying. The oven drying temperature is 40°C to 90°C, and the drying time is 12h to 24h. The blank is then sintered in a high-temperature sintering furnace and calcined at a higher temperature for a certain period of time to form better strength and other properties and to enable the additives to enhance the performance of the blank, thereby obtaining a high-strength water-soluble composite salt core.

[0080] The sintering process of the present invention adopts a combination of distributed sintering and liquid phase sintering, and the final sintering temperature is 450-1200°C. The specific sintering steps are: heating the green body to 360°C at a heating rate of 1-3°C / min, and keeping it warm for 60 minutes to remove the binder and other organic matter in the green body; then heating at a heating rate of 1-3°C / min, keeping it warm at 5-30°C from the final sintering temperature, and the keeping time is 30-60 minutes; then heating to the final sintering temperature at a heating rate of 5°C / min, and keeping it warm for 10-30 minutes; then cooling to 5-30°C below the final sintering temperature, and continuing to keep it warm for 30-60 minutes; finally cooling to room temperature with the furnace. The purpose of using liquid phase sintering is to improve the bending strength of the salt core and avoid over-sintering.

[0081] The method of preparing a water-soluble composite salt core by 3D printing of a slurry for direct writing of low-melting-point alloy casting of the present invention can utilize graphite powder (burned out at 500-600°C) as a supporting matrix material, and adopts a multi-extrusion head 3D printing to form a complex structure salt core, which can be made into a suspended structure water-soluble composite salt core after high-temperature sintering, so as to be applied to aluminum alloy components with complex internal structures and suspended channels. Among them, the direct writing forming equipment is a prior art, such as the 3D printing device recorded in the patent number CN202311075788.8 and the patent name A dual-head collaborative direct writing 3D printing device, which can be used as a specific embodiment of the heatable direct writing 3D printing device of the present invention.

[0082] It should be noted that Examples 1-8 all use the direct writing forming equipment independently built by the inventor, the computer-side control software is the simplify 3D slicing software, and the size of the printed body is 60 mm×10 mm×6 mm.

[0083] <Example 1>

[0084] The interfacial binding energy of NaCl(100) / Na2CO3(100) was calculated to be 13.2 J / m by first principle calculation. 2 , a water-soluble composite salt core was prepared using NaCl-Na2CO3 as the matrix material.

[0085] A method for preparing a water-soluble composite salt core by 3D printing of slurry for low melting point alloy casting, comprising the following steps:

[0086] Use deionized water to prepare a 10% polyvinyl alcohol aqueous solution, and mix sodium chloride (D50 = 10μm) and sodium carbonate (D50 = 6.5μm) in a ratio of 30mol% NaCl-70mol% Na2CO3. Use silicone solution to coat the mixed powder to obtain a pretreated water-soluble inorganic salt. Mix 66 parts by mass of pretreated water-soluble inorganic salt, 34.4 parts by mass of polyvinyl alcohol aqueous solution, 0.5 parts by mass of ammonium polyacrylate, and 0.1 parts by mass of defoamer in a container to obtain a premixed solution. Transfer the premixed solution to a ball mill, add ball mill beads, place it in a spherical ball mill for 13h, and take it out to obtain a uniformly dispersed salt-based slurry.

[0087] The printing process parameters were set on the computer slice software that controlled the slurry direct writing equipment: the filling rate was 100%, the printing speed was 600mm / min, and the filling line angle was 23° / -67° composite filling. The ball-milled salt-based slurry was loaded into the extrusion barrel, and a 0.51mm extruder head was selected for printing. The extrusion pressure was 5psi, and the printed body was deposited on a substrate that was pre-coated with dimethyl silicone oil. The body was removed from the substrate, placed in the air to dry naturally for 24 hours, and then transferred to a drying oven and dried at 70°C for 24 hours.

[0088] The dried green body is sintered in a high-temperature sintering furnace. The sintering program is set on the control panel of the high-temperature sintering furnace: starting from room temperature, heating at a heating rate of 1°C / min, heating to 360°C and keeping it for 60 minutes; then heating at a heating rate of 3°C / min, heating to 600°C and keeping it for 60 minutes; then heating to 620°C at a heating rate of 5°C / min and keeping it for 30 minutes; then cooling to 600°C and keeping it for 60 minutes; finally cooling to room temperature with the furnace. After sintering, the final water-soluble composite salt core product is obtained.

[0089] <Example 2>

[0090] The interfacial binding energy of NaCl(100) / K2CO3(011) was calculated to be 1.04 J / m by first principle calculation. 2 , a water-soluble composite salt core was prepared using NaCl / K2CO3 as the matrix material.

[0091] A method for preparing a water-soluble composite salt core by 3D printing of slurry for low melting point alloy casting, comprising the following steps:

[0092] Use deionized water to prepare a 20% polyethylene glycol aqueous solution, and mix sodium chloride (D50 = 10μm) and potassium carbonate (D50 = 5μm) in a ratio of 50mol% NaCl-50mol% K2CO3. Use silicone solution to coat the mixed powder to obtain a pretreated water-soluble inorganic salt. Mix 71 parts by mass of mixed inorganic salt powder, 28.4 parts by mass of polyethylene glycol aqueous solution, 0.5 parts by mass of ammonium polyacrylate, and 0.1 parts by mass of defoaming agent in a container to obtain a premixed solution. Transfer the premixed solution to a ball mill, add ball milling beads, place it in a ball mill for 13h, and take it out to obtain a uniformly dispersed salt base slurry.

[0093] The printing process parameters were set on the computer slicer software that controlled the slurry direct writing equipment: the filling rate was 100%, the printing speed was 600mm / min, and the filling line angle was 45° / -45° composite filling. The ball-milled salt-based slurry was loaded into the extrusion barrel, and a 0.61mm extruder head was selected for printing. The extrusion pressure was 10psi, and the printed body was deposited on a substrate that was pre-coated with dimethyl silicone oil. The body was removed from the substrate, placed in the air to dry naturally for 24 hours, and then transferred to a drying oven and dried at 70°C for 24 hours.

[0094] The dried green body is sintered in a high-temperature sintering furnace. The sintering program is set on the control panel of the high-temperature sintering furnace: starting from room temperature, heating at a heating rate of 1°C / min, heating to 360°C and keeping it warm for 60 minutes; then heating at a heating rate of 3°C / min, heating to 620°C and keeping it warm for 60 minutes; then heating to 640°C at a heating rate of 5°C / min and keeping it warm for 30 minutes; then cooling to 620°C and keeping it warm for 60 minutes; finally cooling to room temperature with the furnace. After sintering, the final water-soluble composite salt core product is obtained.

[0095] <Example 3>

[0096] The interfacial binding energy of NaCl(100) / CaCO3(010) was calculated to be 0.12 J / m 2 , NaCl-CaCO3 was used as the matrix material to prepare the water-soluble composite salt core.

[0097] A method for preparing a water-soluble composite salt core by 3D printing of slurry for low melting point alloy casting, comprising the following steps:

[0098] Use deionized water to prepare a 2% methylcellulose aqueous solution, and mix sodium chloride (D50 = 10μm) and calcium carbonate (D50 = 5μm) in a ratio of 60mol% NaCl-40mol% CaCO3. Use an organosilicon solution to coat the mixed powder to obtain a pretreated water-soluble inorganic salt, wherein the mass ratio of the inorganic salt powder system to the organosilicon solution is 4:6. 76 parts by mass of the pretreated water-soluble inorganic salt, 22.4 parts by mass of the methylcellulose aqueous solution, 1.5 parts by mass of ammonium polyacrylate, and 0.1 parts by mass of the defoaming agent are mixed and stirred in a container to obtain a premixed solution. The premixed solution is transferred to a ball mill, ball milling beads are added, and the mixture is placed in a ball mill for 13h. After taking it out, a uniformly dispersed salt-based slurry is obtained.

[0099] The printing process parameters were set on the computer slicer software that controlled the slurry direct writing equipment: the filling rate was 100%, the printing speed was 600mm / min, and the filling line angle was 0° / 90° composite filling. The ball-milled salt-based slurry was loaded into the extrusion barrel, and a 0.41mm extruder head was selected for printing. The extrusion pressure was 20psi, and the printed body was deposited on a substrate that was pre-coated with dimethyl silicone oil. The body was removed from the substrate, placed in the air to dry naturally for 24 hours, and then transferred to a drying oven and dried at 70°C for 24 hours.

[0100] The dried green body is sintered in a high-temperature sintering furnace. The sintering program is set on the control panel of the high-temperature sintering furnace: starting from room temperature, heating at a heating rate of 1°C / min, heating to 360°C and keeping it warm for 60 minutes; then heating at a heating rate of 3°C / min, heating to 770°C and keeping it warm for 60 minutes; then heating to 790°C at a heating rate of 5°C / min and keeping it warm for 30 minutes; then cooling to 770°C and keeping it warm for 60 minutes; finally cooling to room temperature with the furnace. After sintering, the final water-soluble composite salt core product is obtained.

[0101] <Example 4>

[0102] The interfacial binding energy of NaCl(100) / KCl(101) was calculated to be 0.05 J / m by first principle calculation. 2 , using NaCl-KCl as the matrix material to prepare the water-soluble composite salt core.

[0103] A method for preparing a water-soluble composite salt core by 3D printing of slurry for low melting point alloy casting, comprising the following steps:

[0104] Use deionized water to prepare a 3% epoxy resin aqueous solution, and mix sodium chloride (D50 = 10μm) and potassium chloride (D50 = 5μm) in a ratio of 50mol% NaCl-50mol% KCl. Use an organosilicon solution to coat the mixed powder to obtain a pretreated water-soluble inorganic salt, wherein the mass ratio of the inorganic salt powder system to the organosilicon solution is 4:6. 73 parts by mass of the pretreated water-soluble inorganic salt, 25.9 parts by mass of the epoxy resin aqueous solution, 1 part by mass of ammonium polyacrylate, and 0.1 parts by mass of the defoamer are mixed and stirred in a container to obtain a premixed solution. The premixed solution is transferred to a ball mill, ball milling beads are added, and the mixture is placed in a ball mill for 13h. After taking it out, a uniformly dispersed salt-based slurry is obtained.

[0105] The printing process parameters were set on the computer slice software that controlled the slurry direct writing equipment: the filling rate was 100%, the printing speed was 600mm / min, and the filling line angle was 45° / -45° composite filling. The ball-milled salt-based slurry was loaded into the extrusion barrel, and a 0.51mm extruder head was selected for printing. The extrusion pressure was 15psi, and the printed body was deposited on a substrate that was pre-coated with dimethyl silicone oil. The body was removed from the substrate, placed in the air to dry naturally for 24 hours, and then transferred to a drying oven and dried at 70°C for 24 hours.

[0106] The dried green body is sintered in a high-temperature sintering furnace. The sintering program is set on the control panel of the high-temperature sintering furnace: starting from room temperature, heating at a heating rate of 1°C / min, heating to 360°C and keeping it for 60 minutes; then heating at a heating rate of 3°C / min, heating to 660°C and keeping it for 60 minutes; then heating to 680°C at a heating rate of 5°C / min and keeping it for 30 minutes; then cooling to 660°C and keeping it for 60 minutes; finally cooling to room temperature with the furnace. After sintering, the final water-soluble composite salt core product is obtained.

[0107] <Example 5>

[0108] The interfacial binding energy of NaCl(100) / Na2CO3(100) / MgCl2(100) was calculated to be 14.03 J / m by first principle. 2 , a water-soluble composite salt core was prepared using NaCl-Na2CO3-MgCl2 as the matrix material.

[0109] A method for preparing a water-soluble composite salt core by 3D printing of slurry for low melting point alloy casting, comprising the following steps:

[0110] Use anhydrous ethanol to prepare a polyvinyl pyrrolidone solution with a mass fraction of 12.5%, and mix sodium chloride (D50 = 10μm), sodium carbonate (D50 = 6.5μm), and magnesium chloride (D50 = 5μm) in a ratio of 25mol% NaCl-58mol% Na2CO3-17mol% MgCl2. Use an organic silicon solution to coat the mixed powder to obtain a pretreated water-soluble inorganic salt, wherein the mass ratio of the inorganic salt powder system to the organic silicon solution is 5:5. 71 parts by mass of the pretreated water-soluble inorganic salt, 27.9 parts by mass of the polyvinyl pyrrolidone solution, 1 part by mass of ammonium polyacrylate, and 0.1 parts by mass of the defoaming agent are mixed and stirred in a container to obtain a premixed solution. The premixed solution is transferred to a ball mill, ball milling beads are added, and the mixture is placed in a ball mill for 13h. After taking it out, a uniformly dispersed salt-based slurry is obtained.

[0111] The printing process parameters were set on the computer slice software that controlled the slurry direct writing equipment: the filling rate was 100%, the printing speed was 600mm / min, and the filling line angle was 45° / -45° composite filling. The ball-milled salt-based slurry was loaded into the extrusion barrel, and a 0.61mm extruder head was selected for printing. The extrusion pressure was 40psi, and the printed body was deposited on a substrate that was pre-coated with dimethyl silicone oil. The body was removed from the substrate, placed in the air to dry naturally for 24 hours, and then transferred to a drying oven and dried at 70°C for 24 hours.

[0112] The dried green body is sintered in a high-temperature sintering furnace. The sintering program is set on the control panel of the high-temperature sintering furnace: starting from room temperature, heating at a heating rate of 1°C / min, heating to 360°C and keeping it for 60 minutes; then heating at a heating rate of 3°C / min, heating to 420°C and keeping it for 60 minutes; then heating to 450°C at a heating rate of 5°C / min and keeping it for 30 minutes; then cooling to 420°C and keeping it for 60 minutes; finally cooling to room temperature with the furnace. After sintering, the final water-soluble composite salt core product is obtained.

[0113] <Example 6>

[0114] The interfacial binding energy of NaCl(100) / Na2CO3(100) / CaCl2(110) was calculated to be 16.06 J / m 2 , a water-soluble composite salt core was prepared using NaCl-Na2CO3-CaCl2 as the matrix material.

[0115] A method for preparing a water-soluble composite salt core by 3D printing of slurry for low melting point alloy casting, comprising the following steps:

[0116] Use anhydrous ethanol to prepare a polyvinyl pyrrolidone solution with a mass fraction of 12.5%, and mix sodium chloride (D50 = 10μm), sodium carbonate (D50 = 6.5μm), and calcium chloride (D50 = 5μm) in a ratio of 25mol% NaCl-58mol% Na2CO3-17mol% BaCl2. Use an organic silicon solution to coat the mixed powder to obtain a pretreated water-soluble inorganic salt, wherein the mass ratio of the inorganic salt powder system to the organic silicon solution is 5:5. 71 parts by mass of the pretreated water-soluble inorganic salt, 27.9 parts by mass of the polyvinyl pyrrolidone solution, 1 part by mass of ammonium polyacrylate, and 0.1 parts by mass of the defoaming agent are mixed and stirred in a container to obtain a premixed solution. The premixed solution is transferred to a ball mill, ball milling beads are added, and the mixture is placed in a ball mill for 13h. After taking it out, a uniformly dispersed salt-based slurry is obtained.

[0117] The printing process parameters were set on the computer slice software that controlled the slurry direct writing equipment: the filling rate was 100%, the printing speed was 600mm / min, and the filling line angle was 45° / -45° composite filling. The ball-milled salt-based slurry was loaded into the extrusion barrel, and a 0.84mm extruder head was selected for printing. The extrusion pressure was 40psi, and the printed body was deposited on a substrate that was pre-coated with dimethyl silicone oil. The body was removed from the substrate, placed in the air to dry naturally for 24 hours, and then transferred to a drying oven and dried at 70°C for 24 hours.

[0118] The dried green body is sintered in a high-temperature sintering furnace. The sintering program is set on the control panel of the high-temperature sintering furnace: starting from room temperature, heating at a heating rate of 1°C / min, heating to 360°C and keeping it for 60 minutes; then heating at a heating rate of 3°C / min, heating to 600°C and keeping it for 60 minutes; then heating to 630°C at a heating rate of 5°C / min and keeping it for 30 minutes; then cooling to 600°C and keeping it for 60 minutes; finally cooling to room temperature with the furnace. After sintering, the final water-soluble composite salt core product is obtained.

[0119] <Example 7>

[0120] The first principle calculations revealed that the interface binding energy of NaCl / Na2CO3 / BaCl2 is 37 J / m 2 , a water-soluble composite salt core was prepared using NaCl-Na2CO3-BaCl2 as the matrix material.

[0121] A method for preparing a water-soluble composite salt core by 3D printing of slurry for low melting point alloy casting, comprising the following steps:

[0122] Use anhydrous ethanol to prepare a polyvinyl pyrrolidone solution with a mass fraction of 12.5%, and mix sodium chloride (D50 = 10μm), sodium carbonate (D50 = 6.5μm) and barium chloride (D50 = 5μm) in a ratio of 25mol% NaCl-58mol% Na2CO3-17mol% BaCl2. Use an organic silicon solution to coat the mixed powder to obtain a pretreated water-soluble inorganic salt, wherein the mass ratio of the inorganic salt powder system to the organic silicon solution is 5:5. 68 parts by mass of the pretreated water-soluble inorganic salt, 30.9 parts by mass of the polyvinyl pyrrolidone solution, 1 part by mass of ammonium polyacrylate, and 0.1 parts by mass of the defoaming agent are mixed and stirred in a container to obtain a premixed solution. The premixed solution is transferred to a ball mill, ball milling beads are added, and the mixture is placed in a ball mill for 13h. After taking it out, a uniformly dispersed salt-based slurry is obtained.

[0123] The printing process parameters were set on the computer slice software that controlled the slurry direct writing equipment: the filling rate was 100%, the printing speed was 600mm / min, and the filling line angle was 45° / -45° composite filling. The ball-milled salt-based slurry was loaded into the extrusion barrel, and a 0.51mm extruder head was selected for printing. The extrusion pressure was 30psi, and the printed body was deposited on a substrate that was pre-coated with dimethyl silicone oil. The body was removed from the substrate, placed in the air to dry naturally for 24 hours, and then transferred to a drying oven and dried at 70°C for 24 hours.

[0124] The dried green body is sintered in a high-temperature sintering furnace. The sintering program is set on the control panel of the high-temperature sintering furnace: starting from room temperature, heating at a heating rate of 1°C / min, heating to 360°C and keeping it for 60 minutes; then heating at a heating rate of 3°C / min, heating to 600°C and keeping it for 60 minutes; then heating to 630°C at a heating rate of 5°C / min and keeping it for 30 minutes; then cooling to 600°C and keeping it for 60 minutes; finally cooling to room temperature with the furnace. After sintering, the final water-soluble composite salt core product is obtained.

[0125] <Example 8>

[0126] The first principle calculations revealed that the interface binding energy of NaCl / Na2CO3 / BaCl2 is 37 J / m 2 , NaCl-Na2CO3-BaCl2 is used as the matrix material to prepare the water-soluble composite salt core, and graphite powder is used as the matrix material to prepare the supporting material of the water-soluble composite salt core.

[0127] A method for preparing a water-soluble composite salt core by 3D printing of slurry for low melting point alloy casting, comprising the following steps:

[0128] Use anhydrous ethanol to prepare a polyvinyl pyrrolidone solution with a mass fraction of 12.5%, and mix sodium chloride (D50 = 10μm), sodium carbonate (D50 = 6.5μm) and barium chloride (D50 = 5μm) in a ratio of 25mol% NaCl-58mol% Na2CO3-17mol% BaCl2. Use silicone solution to coat the mixed powder to obtain a pretreated water-soluble inorganic salt. 68 parts by mass of pretreated water-soluble inorganic salt, 30.9 parts by mass of polyvinyl pyrrolidone solution, 1 part by mass of ammonium polyacrylate, and 0.1 parts by mass of defoaming agent are mixed and stirred in a container to obtain a premixed solution. Transfer the premixed solution to a ball mill, add ball milling beads, place it in a ball mill for 13h, and take it out to obtain a uniformly dispersed salt base slurry.

[0129] Graphite powder (D50 = 5 μm) was coated with an organosilicon solution to obtain pretreated graphite powder, wherein the mass ratio of graphite powder to organosilicon solution was 6:4. 72 parts by mass of pretreated graphite powder, 26.9 parts by mass of polyvinyl pyrrolidone solution, 1 part by mass of ammonium polyacrylate, and 0.1 parts by mass of defoamer were mixed and stirred evenly in a container to obtain a premixed graphite slurry. The premixed graphite slurry was transferred to a ball mill, ball milling beads were added, and the mixture was placed in a ball mill for 13 hours, and then a uniformly dispersed graphite-based slurry was obtained after being taken out.

[0130] The printing process parameters were set in the host computer slicing software of the dual extruder 3D printing device: the filling rate was 100%, the printing speed was 600mm / min, and the filling routing angle was 45° / -45° composite filling. The evenly stirred salt-based slurry and graphite-based slurry were loaded into two extrusion barrels respectively, and a 0.61mm extruder head was used for printing. The extrusion pressure was 30psi, and the printed body was deposited on a substrate coated with dimethyl silicone oil in advance. The body was removed from the substrate, placed in the air to dry naturally for 24 hours, and then transferred to a drying oven and dried at 70°C for 24 hours.

[0131] The dried green body is sintered in a high-temperature sintering furnace. The sintering program is set on the control panel of the high-temperature sintering furnace: starting from room temperature, heating at a heating rate of 1°C / min, heating to 360°C and keeping it for 60 minutes; then heating at a heating rate of 3°C / min, heating to 600°C and keeping it for 60 minutes; then heating to 630°C at a heating rate of 5°C / min and keeping it for 30 minutes; then cooling to 600°C and keeping it for 60 minutes; finally cooling to room temperature with the furnace. After sintering, the final water-soluble composite salt core product is obtained.

[0132] <Comparative Example 1>

[0133] Sodium chloride (D50 = 10 μm) and sodium carbonate (D50 = 6.5 μm) are uniformly mixed in a ratio of 30 mol% NaCl-70 mol% Na2CO3 to obtain an inorganic salt powder system;

[0134] Use anhydrous ethanol to prepare a polyvinyl pyrrolidone solution with a mass fraction of 12.5%, and mix the inorganic salt powder system and the polyvinyl pyrrolidone solution in a mass ratio of 8:2 to obtain a mixed slurry. Slowly pour the mixed slurry into the mold, let it stand for a while, and after the slurry is solidified and formed, demold it to obtain a wet blank.

[0135] The wet blank was placed in a drying oven and dried at 80°C for 12 hours to obtain a dry blank, which was sintered in a step-by-step sintering manner to obtain a sintered body. The specific sintering steps were as follows: first, heated from room temperature to 200°C at a heating rate of 1°C / min, then heated from 200°C to 300°C at a heating rate of 0.5°C / min, and then heated from 300°C to 360°C at a heating rate of 0.75°C / min, and kept at 360°C for 60 minutes; then heated at a heating rate of 3°C / min to 600°C and kept for 60 minutes; then heated to 620°C at a heating rate of 5°C / min and kept for 30 minutes; then cooled to 600°C and kept for 60 minutes; finally cooled to room temperature with the furnace. After sintering, the final water-soluble composite salt core product was obtained.

[0136] The water-soluble composite salt cores prepared in Examples 1-8 were tested for performance, and the results are shown in Table 9:

[0137] Table 9 Water-soluble composite salt core experimental data

[0138]

[0139]

[0140] In summary, Examples 1-8 are water-soluble composite salt cores prepared by the present invention. Compared with the water-soluble composite salt core material prepared in Comparative Example 1, the water-soluble composite salt cores of Examples 1-8 have good bending strength, high surface quality, excellent water solubility rate and low moisture absorption rate, and have excellent comprehensive performance, which can meet the process requirements of precision casting of complex parts.

[0141] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A water-soluble composite salt core material for low melting point alloy casting, characterized in that: It is composed of the following components: Pre-treat water-soluble inorganic salts, binders and additives, wherein the pre-treat water-soluble inorganic salts are obtained by mixing a coating solution with inorganic salt powder, and in terms of mass percentage, pre-treat water-soluble inorganic salts: binder: additives = 60%-80%: 20%-30%: 0%-10%.

2. The water-soluble composite inorganic salt material according to claim 1, characterized in that: The mass percentage of the inorganic salt powder and the coating solution is 40%-60%: 40%-60%.

3. The water-soluble composite inorganic salt material according to claim 2, characterized in that: The inorganic salt powder includes two or more of sodium sulfate, potassium sulfate, sodium carbonate, potassium carbonate, calcium carbonate, sodium chloride, potassium chloride, magnesium chloride, calcium chloride or barium chloride, and the melting point of the inorganic salt powder is 450-1200° C.; The particle size of the inorganic salt powder is 500-3000 mesh; The coating solution is prepared from polydimethylsiloxane and anhydrous ethanol.

4. The water-soluble composite inorganic salt material according to claim 1, characterized in that: The binder is one of polyvinyl alcohol aqueous solution, polyethylene glycol aqueous solution, polyacrylamide aqueous solution, methyl cellulose aqueous solution, epoxy resin aqueous solution, polyvinyl pyrrolidone-anhydrous ethanol solution, and polyacrylic acid-anhydrous ethanol, and the concentration of the binder solution is 1% to 25%.

5. The water-soluble composite inorganic salt material according to claim 1, characterized in that: The additive is a mixture of an enhancer, a dispersant and a defoamer, and the weight percentage is as follows: enhancer: dispersant: defoamer = 97.5%-99.5%: 0.5%-1.5%: 0%-1%; The reinforcing agent is one or more of bauxite powder, corundum powder, mullite powder, zirconium oxide powder, quartz powder, titanium oxide powder, sericite or glass fiber, and the particle size of the reinforcing agent is 300-1250 meshes; The dispersant is one of ammonium polyacrylate or sodium dodecylbenzene sulfonate; The defoaming agent is a silicone defoaming agent.

6. A method for preparing a water-soluble composite salt core by 3D printing of slurry for low melting point alloy casting, characterized in that: The specific steps include: S1. 3D printing of the salt core blank: preparing salt-based raw materials, grinding the salt-based raw materials sufficiently to obtain salt-based slurry, and using slurry direct writing forming equipment to 3D print the salt-based slurry to obtain a salt core blank; Wherein, the salt-based raw material is the water-soluble composite salt core material or a mixture of a binder and a dispersant as described in any one of claims 1 to 5; The inner diameter of the printing needle is 0.41mm~1.55mm, and the extrusion pressure is 5psi~50psi; S2. Sintering of the water-soluble composite salt core: The salt core blank is subjected to natural drying, baking and sintering treatments in sequence to obtain a water-soluble composite salt core.

7. The preparation method according to claim 6, characterized in that: In step S1, when the salt-based raw material is a water-soluble composite salt core material, the preparation method of the salt-based slurry is: The inorganic salt powder is coated with a coating solution to obtain a pretreated water-soluble inorganic salt, and the pretreated water-soluble inorganic salt, a binder solution and an additive are uniformly mixed to obtain a premixed solution, wherein the additive is a mixture of a reinforcing agent, a dispersant and a defoaming agent, and the mass percentage of each component is as follows: Pretreatment water-soluble inorganic salt: binder: additive = 60%-80%: 20%-30%: 0%-10%.

8. The preparation method according to claim 6, characterized in that: In step S1, when the salt-based raw material is a mixture of a binder and a dispersant, graphite powder is added to the mixture, and the mass percentages of the graphite powder, the binder and the dispersant are 70%-75%: 24%-29.5%: 0.5%-1% in terms of mass percentage.

9. The preparation method according to claim 8, characterized in that: and: The dispersant is one of ammonium polyacrylate or sodium dodecylbenzene sulfonate; The binder is one of polyvinyl alcohol aqueous solution, polyethylene glycol aqueous solution, polyacrylamide aqueous solution, methyl cellulose aqueous solution, epoxy resin aqueous solution, polyvinyl pyrrolidone-anhydrous ethanol solution and polyacrylic acid-anhydrous ethanol.

10. The preparation method according to claim 6, characterized in that: In step S2, the drying temperature is 40°C to 90°C, and the drying time is 12h to 24h; the sintering is a combination of step-by-step sintering and liquid phase sintering, and the final sintering temperature is 450 to 1200°C.

Citation Information

Patent Citations

  • Water-soluble graphite composited salt core material, graphite composited salt core and preparation method thereof

    CN104399865A

  • Double-head collaborative direct-writing type 3D printing device and method

    CN117261207A

  • High-strength composite salt core material for low-melting-point alloy casting, salt core and preparation method

    CN106670376A

  • Casting mold material, production method for casting mold material, and production method for casting mold

    CN111511481A

  • Method for producing moulds and cores suitable for producing fibre composite bodies or cast parts in metal or plastic, mould base material and binder used in method and moulds and cores produced according to method

    CN112166000A

Cited By

  • Ceramic salt core for high-pressure casting of refrigerant runner plate

    CN120551325A